AIS data to inform small scale fisheries management and marine spatial planning - James, Mark; Mendo, Tania; Jones, Esther L.; Orr, Kyla; McKnight, Ali; Thompson, John (Marine policy, 2018)
Automatic Identification Systems (AIS) are collision avoidance devices used on-board both commercial and leisure craft. These systems report the position, track and speed of the vessel through Very High Frequency radio transmissions which are accessible to any suitable receiver. This paper explores the potential to use AIS data to inform small scale fisheries management and marine spatial planning. First, the propagation and reception of the line of sight AIS transmissions was modelled around the coast of Scotland to identify areas where the use of AIS may be compromised. Using open source Geographic Information System and relational database software, computationally efficient methods of processing and analysing AIS data were explored. Three months of AIS data derived from 274 Scottish small scale fishing vessels were used to provide spatio-temporal analyses of trip duration and distance travelled, location of fishing activities, and vessel dependency on fishing grounds. The coverage, opportunities and challenges of using AIS are discussed together with broader applications and future developments. •Model predicts AIS data reception in the majority of Scottish coastal waters.•Open source software provides a useful and effective platform for AIS data analyses.•AIS data facilitates incorporation of small scale fisheries into spatial planning.•AIS data useful to characterise fishing trips and most important fishing grounds.•Important limitations of using AIS data for regulatory purposes identified.